Comparison of stroke- and bleed-related healthcare resource utilization and costs among patients with newly diagnosed non-valvular atrial fibrillation and newly treated with dabigatran, rivaroxaban, or warfarin. (4th March 2019) - Gilligan, Adrienne M.; Franchino-Elder, Jessica; Song, Xue; Wang, Cheng; Henriques, Caroline; Sainski-Nguyen, Amy; Wilson, Kathleen; Smith, David M.; Sander, Stephen
ABSTRACT: Background : This is one of the first head-to-head real-world evidence studies comparing stroke-related and bleed-related healthcare and resource utilization (HCRU) and costs among non-valvular atrial fibrillation (NVAF) patients initiating oral anticoagulants. Methods : Adult NVAF patients newly diagnosed and treated with dabigatran, rivaroxaban, or warfarin between 10/01/2010 and 12/31/2014 were identified using MarketScan Commercial and Medicare Supplemental databases. Per-patient-per-month stroke and bleed-related HCRU and costs were reported. Results : Dabigatran patients were matched 1:1 to 26, 592 rivaroxaban and 33, 024 warfarin patients (mean age=68 years). Compared to rivaroxaban, dabigatran patients had lower bleed-related inpatient and outpatient HCRU (0.004 vs. 0.005; 0.099 vs. 0.145) and significantly lower adjusted bleed-related costs (116 vs. 172), all p <0.05. Compared to warfarin, dabigatran patients had significantly lower stroke-related outpatient visits (0.034 vs. 0.048, p <0.001) and higher bleed-related outpatient visits (0.101 vs. 0.091, p =0.045). Multivariate adjusted bleed-related costs were significantly lower for dabigatran patients than warfarin patients (94 vs. 138, p <0.001). Conclusions : The results suggest that dabigatran patients had lower bleed-related HCRU and costs than rivaroxaban patients, and lower outpatient stroke-related HCRU, higher bleed-related outpatient HCRU, and lower bleed-related costs than warfarin patients. It provides valuable stroke-related and bleed-related HCRU and costs information among commercially insured and Medicare patients.